2009
DOI: 10.1080/07294360802444370
|View full text |Cite
|
Sign up to set email alerts
|

Gender and higher education experience: a case study

Abstract: This research seeks to contribute to current discussion of gender differences in experience of higher education. Its specific focus is to compare the assessment of various university services by male and female students. The research sample consisted of 9793 students who participated in three University of Western Sydney surveys in 2004 and 2005. The results suggest that, first, female students place higher importance on the majority of the university's services than do male students; second, as female student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 8 publications
2
38
0
1
Order By: Relevance
“…Previous research has shown that it is not so much the cognitive learner characteristics that explain gender differences in study success, but it is the non-cognitive characteristics such as discipline, motivation, time management skills and goals that are important (Trueman and Hartley 1996;Grebennikov and Skaines 2009;Sommers 2001;Evers and Mancuso 2006;Jorgensen et al 2009). On average, women more often show the motivation, discipline skills and time management skills that are important for performing well in higher education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that it is not so much the cognitive learner characteristics that explain gender differences in study success, but it is the non-cognitive characteristics such as discipline, motivation, time management skills and goals that are important (Trueman and Hartley 1996;Grebennikov and Skaines 2009;Sommers 2001;Evers and Mancuso 2006;Jorgensen et al 2009). On average, women more often show the motivation, discipline skills and time management skills that are important for performing well in higher education.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, gender differences in higher education are related to goals. Grebennikov and Skaines (2009) argue on the basis of their literature review that women find academic goals more important than men and they place a greater value on higher education, mainly because women need to better prepare themselves in order to have the same chances on the job market. The OECD report (2008) also shows that girls seem to have higher aspirations than boys.…”
Section: Learner Characteristicsmentioning
confidence: 99%
“…64% of the papers reviewed are concerned with the objectives of gaining a better understanding of the student experience (Campbell and Li, 2008;Chahal and Devi, 2013;Chapman and Pyvis, 2006;Ellis et al, 2004;Geall, 2000;Grebennikov and Skaines, 2009;Kim, 2007;Ng and Forbes, 2009;Peterson and Miller, 2004;Shanahan and Gerber, 2004, Tam, 2007, Voss, 2009Wilkins and Balakrishnan, 2013;Yeo, 2009) and studying the impact of higher education service attributes on the student experience (Arambewela and Maringe, 2012;Baird and Gordon, 2009;Baranova et al, 2011;Douglas et al, 2008;Duarte et al, 2012;Gift and Bell-Hutchinson, 2007;Gosling and D'Andrea, 2001;Peltier et al, 2007;Scaffidi and Berman, 2011;Simpson and Tan, 2009;Stake and Malkin, 2003;Ward et al, 2010). The former objective predominantly mentions the exploration of learning and student experiences, and satisfaction with service encounters in higher education; while the emphasis of the latter objective is to identify factors which influence student experiences as well as to develop frameworks which illustrate the relationship between these factors and student experiences.…”
Section: Purposes Of Existential Researchmentioning
confidence: 99%
“…For the time period of 2000 to 2014 (inclusive), papers published in this category of research focused on the identification of differences in responses between males and females (Grace et al, 2012;Grebennikov and Skaines, 2009). Grace et al (2012) category is scant, studies on differences in higher education experiences between gender will help higher education institutions to "take appropriate action to ensure the quality of the learning environment for all students" (Grebennikov and Skaines, 2009, p.73).…”
Section: Gender Differences In Assessment Of Higher Education Experiencementioning
confidence: 99%
See 1 more Smart Citation